2017
DOI: 10.1177/2158244016682996
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Academic Benefits of the Advanced Placement Program

Abstract: With more than 3 million participants per year, the Advanced Placement (AP) program is one of the most popular programs in the United States for exposing high-achieving high school students to advanced academic content. Sponsored by the College Board, the AP program provides a framework in which high school teachers can teach introductory college-level courses to high school students. These students then take one of 34 standardized tests at the end of the year, and students who score well on their course’s AP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…One of the famous gifted programs in America [15], [16] uses Scholastic Assessment Test (SAT) as the systems to measure the skills and knowledges of students who will continue their study in higher education. [17], the test consists of two main parts; language and math. Then, the component of SAT divided into three parts: Reading, 2) Writing and Language, 3) Math, and Esay SAT (optional) [18], [19].…”
Section: Gifted Measurement At This Timementioning
confidence: 99%
See 1 more Smart Citation
“…One of the famous gifted programs in America [15], [16] uses Scholastic Assessment Test (SAT) as the systems to measure the skills and knowledges of students who will continue their study in higher education. [17], the test consists of two main parts; language and math. Then, the component of SAT divided into three parts: Reading, 2) Writing and Language, 3) Math, and Esay SAT (optional) [18], [19].…”
Section: Gifted Measurement At This Timementioning
confidence: 99%
“…64 year 2014. This program is created by adopting the popular program in America namely Advance Placement [47], [15], [48], in which that program consists of three models; specialization, cross interest and deepening interest [49], [50]. Unfortunately, the decision which is taken by the government seems to be in a hurry.…”
Section: Pro-contra Gifted Students Program Developmentmentioning
confidence: 99%
“…Studies have also found that students who take advanced courses in high school, such as AP courses, tend to outperform students who do not (Keng & Dodd, 2008). Geiser and Santelices (2004), Klopfenstein and Thomas (2005), Sadler and Tai (2007b), Warne (2017), and Warne, Nagaishi, Slade, Hermesmeyer, and Peck (2014) found that the strength of the relationship between advanced course participation and college achievement depends on the additional covariates in the model. An unresolved question is the correct methodological approach to estimating how GPAs should be weighted by course type.…”
Section: Previous Research On the Validity Of The High School Gpamentioning
confidence: 99%
“…Would taking such an upper-level interdisciplinary PBL course as an undergraduate provide a similar "knowledge bridge" to medical school philosophy as does taking high-school AP credits? 20 If the answer is yes, then the other issue is whether junior and senior pre-medical students would be able to master a PBL interdisciplinary biology, biochemistry, and clinical course successfully.…”
Section: Htmentioning
confidence: 99%